POSTER DI RUANG PUBLIK: SUARA PEREMPUAN CALON LEGISLATIF - Yoga Pradana Wicaksono; Sudartomo Macaryus (CARAKA, 2020)
This paper explains the knowledge, attitudes, enthusiasm, and ideology of female legislative candidates as stated in posters in public spaces. Using the theory of critical discourse analysis, this paper explains the characteristics of the contents of the slogans of women legislative candidates. It assumes verbal formulation on posters that are supported by the knowledge, attitudes, enthusiasm, and ideology of legislative candidates who are part of the posters posted in the public space.